TRAF2 protects against cerebral ischemia-induced brain injury by suppressing necroptosis - Li, Jie; Zhang, Jingyu; Zhang, Yusuo; Wang, Zichuang; Song, Yanmei; Wei, Shanwen; He, Meijun; You, Shoujiang; Jia, Jia; Cheng, Jian (Cell death & disease, 2019)
Necroptosis contributes to ischemia-induced brain injury. Tumor necrosis factor (TNF) receptor associated factor 2 (TRAF2) has been reported to suppress necroptotic cell death under several pathological conditions. In this study, we investigated the role of TRAF2 in experimental stroke using a mouse middle cerebral artery occlusion (MCAO) model and in vitro cellular models. TRAF2 expression in the ischemic brain was assessed with western blot and real-time RT-PCR. Gene knockdown of TRAF2 by lentivirus was utilized to investigate the role of TRAF2 in stroke outcomes. The expression of TRAF2 was significantly induced in the ischemic brain at 24 h after reperfusion, and neurons and microglia were two of the cellular sources of TRAF2 induction. Striatal knockdown of TRAF2 increased infarction size, cell death, microglial activation and the expression of pro-inflammatory markers at 24 h after reperfusion. TRAF2 expression and necroptosis were induced in mouse primary microglia treated with conditioned medium collected from neurons subject to oxygen and glucose deprivation (OGD) and in TNFα-treated mouse hippocampal neuronal HT-22 cells in the presence of the pan-caspase inhibitor Z-VAD. In addition, TRAF2 knockdown exacerbated microglial cell death and neuronal cell death under these conditions. Moreover, pre-treatment with a specific necroptosis inhibitor necrostatin-1 (nec-1) suppressed the cell death exacerbated by TRAF2 knockdown in the brain following MCAO, indicating that TRAF2 impacted ischemic brain damage through necroptosis mechanism. Taken together, our results demonstrate that TRAF2 is a novel regulator of cerebral ischemic injury.